Odpowiedzi

2010-01-11T15:35:50+01:00
A) (a+2)*5 = 5a + 10
b) (x+y)(2x-1) = 2x² - x + 2xy - y
c)(x-2y)(x+y) = x² + xy - 2xy - 2y²
d)(4-x)(y+2) = 4y + 8 - xy - 2x
e)(4-2a)(2a+4) = 8a +16 - 4a² - 8a = 16 - 4a²
f)(1/2-3b+4)(4a+2-3b) = 2a - 1 - 2/3b - 12ab - 6b + 9b² + 16a + 8 - 12b
  • Użytkownik Zadane
2010-01-11T15:37:41+01:00
A)5a+10
b)2x2-x+2xy-y
c)x2+xy-2xy-2y2=x2-xy-2y2
d)4y+8-xy-2x
e)8a+16-4a2-8a= 16-4a2
2010-01-11T15:38:05+01:00
A)5a+10
b)2x²-x+2xy-y
c)x²+xy-2xy-2y²
d)4y+8-xy-2x
e)8a+16-4a²-8a
f)10a+5-15/2b-12ab-6b+9b²